Social meaning in the linguistic landscape in Indonesia: literature review - Erma Lestari; Anas Ahmadi; Muhammad Yusi Kamhar (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This article systematically reviews the literature related to social meaning in landscape linguistics. This article aims to study how Language is used to express the identity of a particular ethnic, religious, or social group. Criteria used for choosing included articles in this review are: (a) only related articles on the linguistic landscape in Indonesia and (b) articles taken as data, i.e. 2020-2023. The conclusion from the article Is that landscape linguistics, as a medium that uses Language To convey a message through signs, can work as a medium for embedding values good social for the people who live in it. Based on the explanation above, research about development landscape linguistics, especially in the field of linguistics, must done to add or hone fill from benefit landscape linguistics.